LAYANAN BIMBINGAN KLASIKAL BERBASIS DARING DENGAN METODE EKSPOSITORI TERHADAP PILIHAN KARIR - Eva Farida; Heris Hendriana; Reza Pahlevi (IKIP Siliwangi, 2021)
Classical online-based guidance services at SMP/MTs are one of the types of guidance and counseling services carried out daring the COVID-19 pandemic which requires each individual to study at home, work at home, and worship at home by obeying all the regulations that have been applied. by the government. This study aims to determine the continuity of providing online-based classical guidance services at MTs Al-Bidayah. The approach used instudy thisis a qualitative approach, with the type of qualitative descriptive research. Data collection techniques used in this study were observation and interviews. The subjects used in this study were BK teachers who held students of MTs Al-Bidayah class VIII. The results found that the provision of online-based classical services can be done more interestingly than usual by using the expository method which in the service process provides information on the definitions, principles and concepts of service materials and provides examples of problem solving exercises in the form of lectures, demonstrations , questions and answers and assignments. Keywords: Classical Guidance Service, Career selection.